Thermally driven analog of the Barkhausen effect at the metal-insulator transition in vanadium dioxide - Huber-Rodriguez, Benjamin; Kwang, Siu Yi; Hardy, Will J.; Ji, Heng; Chen, Chih-Wei; Morosan, Emilia; Natelson, Douglas (Applied physics letters, 2014)
The physics of the metal-insulator transition (MIT) in vanadium dioxide remains a subject of intense interest. Because of the complicating effects of elastic strain on the phase transition, there is interest in comparatively strain-free means of examining VO2 material properties. We report contact-free, low-strain studies of the MIT through an inductive bridge approach sensitive to the magnetic response of VO2 powder. Rather than observing the expected step-like change in susceptibility at the transition, we argue that the measured response is dominated by an analog of the Barkhausen effect, due to the extremely sharp jump in the magnetic response of each grain as a function of time as the material is cycled across the phase boundary. This effect suggests that future measurements could access the dynamics of this and similar phase transitions.